Implementación de un sistema de costos por órdenes de producción para el taller “Fuegos Pirotécnicos Ambato”, ubicado en la parroquia Huachi de la provincia de Tungurahua - Martínez Basantes, Sandy Elizabeth (2015)
The information gatheted during during the courseof current investigation it•s important to set the application of a system of production order costs in the workshop “Fireworks pyrotechnic Ambato” since application allowed the owner to determine their actual costs, total and unit, for making better decisions to facilitate the achievement of all goals and objetives for the craft workshop. For getting truly information about the current operation of the pyrotechnic workshop , three research techniques are applied such as: the observation was applied to business, allowing observe directly the facts or events that arise in the workshop, interview with the owner in the order to meet the management and operation there the survey was applied to workers, in order to know the production process in which they operate….